1998
DOI: 10.1063/1.476391
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational relaxation of T1 pyrazine: Results from the refined competitive radiationless decay method

Abstract: Gas phase collisional vibrational relaxation of pyrazine in its lowest triplet electronic state has been further investigated using a refined version of the competitive radiationless decay (CRD) method. Improvements to the experimental apparatus now provide primary kinetic data of much greater accuracy and precision, allowing the use of sample pressures low enough to ensure negligible self-relaxation. A major refinement of the data handling procedure permits the sample’s energy-dependent triplet–triplet molar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Weisman's group has studied collision-induced energy transfer involving pyrazine derivatives in the triplet state. [51][52][53][54] They find that the average energy transferred per collision is significantly higher than that for the ground electronic state 55 at the same vibrational excitation. It was proposed that this is due to the lower vibrational frequencies in the triplet state.…”
Section: B Comparison With Translational Energy Release Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weisman's group has studied collision-induced energy transfer involving pyrazine derivatives in the triplet state. [51][52][53][54] They find that the average energy transferred per collision is significantly higher than that for the ground electronic state 55 at the same vibrational excitation. It was proposed that this is due to the lower vibrational frequencies in the triplet state.…”
Section: B Comparison With Translational Energy Release Distributionmentioning
confidence: 99%
“…[51][52][53][54] They find that the average energy transferred per collision increases rapidly with energy above ϳ2000 cm −1 . At lower energies the amount of energy transferred drops to almost zero.…”
Section: Insensitivity Of the Ter Distributions To The Available Ementioning
confidence: 99%
“…[20][21][22][23][24] Others have monitored the uptake of energy in the bath medium during the relaxation by various techniques [25][26][27][28][29][30][31][32][33][34] or even identified state-specifically the energy transferred, e.g., to CO 2 colliders in single collisions. [35][36][37][38][39][40][41][42] The vast majority of those data are on ͗⌬E͘, the average amount of energy transferred per collision.…”
Section: Introductionmentioning
confidence: 99%
“…Weisman and co-workers studied the energy loss from vibrationally excited triplet state pyrazine using the refined competitive radiationless decay method [124][125]. Their results suggested that the average energy transferred per collision increases rapidly from an apparent threshold that lies between 2000 and 3000 cm À1 .…”
Section: Effects Of Electronic Statementioning
confidence: 97%
“…The enhancement of the methyl group on the energy transfer was always observed for various colliders, including atomic, diatomic and polyatomic molecules [124,125]. Flynn and co-workers studied the energy gain in CO 2 from collisions with highly vibrationally pyrazine and 2-methylpyrazine using high-resolution transient infrared absorption [50,[126][127].…”
Section: Effects Of Methylation and Alkylationmentioning
confidence: 98%